Uncovering the Sex-Specific Endocrine Responses to Reproduction and Parental Care - Austin, Suzanne H.; Krause, Jesse S.; Viernes, Rechelle; Farrar, Victoria S.; Booth, April M.; Harris, Rayna M.; Angelier, Frédéric; Lee, Candice; Bond, Annie; Wingfield, John C.; MacManes, Matthew M.; Calisi, Rebecca M. (Frontiers in Endocrinology, 2021)
Hormones mediate physiological and behavioral changes in adults as they transition into reproduction. In this study, we characterize the circulating levels of five key hormones involved in reproduction in rock doves (Columba livia): corticosterone, progesterone, estradiol, testosterone, and prolactin using univariate and multivariate approaches. We show similar patterns as previous studies in the overall patterns in circulating levels of these hormones, i.e., testosterone (males) and estradiol (females) high during nest-building or egg-laying, prolactin increasing at mid-incubation and peaking at hatching (both sexes), and elevated corticosterone levels in later incubation and early nestling development. In our investigation of hormone co-variation, we find a strong correlation between prolactin and corticosterone across sampling stages and similarities in earlier (early to mid-incubation) compared to later (late incubation to nestling d9) sampling stages in males and females. Finally, we utilized experimental manipulations to simulate nest loss or altered caregiving lengths to test whether external cues, internal timing, or a combination of these factors contributed most to hormone variation. Following nest loss, we found that both males and females responded to the external cue. Males generally responded quickly following nest loss by increasing circulating testosterone, but this response was muted when nest loss occurred early in reproduction. Similar treatment type, e.g., removal of eggs, clustered similarly in hormone space. These results suggest internal drivers limited male response early in reproduction to nest loss. In contrast, circulating levels of these hormones in females either did not change or decreased circulating levels following nest manipulation suggesting responsiveness to external drivers, but unlike males, this result suggests that reproductive processes were decreasing.